Low Protein Diet Improves Meat Quality and Modulates the Composition of Gut Microbiota in Finishing Pigs - Zhu, Cui; Yang, Jingsen; Wu, Qiwen; Chen, Jingping; Yang, Xuefen; Wang, Li; Jiang, Zongyong (Frontiers in Veterinary Science, 2022)
This study investigated the effect of low protein (LP) diet on the growth performance, nitrogen emission, carcass traits, meat quality, and gut microbiota in finishing pigs. Fifty-four barrows (Duroc × Landrace × Yorkshire) were randomly assigned to 3 treatments with 6 replicates (pens) of 3 pigs each. The pigs were fed with either high protein (HP, 16% CP), medium protein (MP, 12% CP), and LP diets (10% CP), respectively. The LP diets did not influence the growth performance, but significantly decreased the plasma urea nitrogen contents and fecal nitrogen emission (P < 0.05). The LP diet significantly decreased the plasma contents of malondialdehyde (MDA), and increased the plasma glutathione (GSH) contents (P < 0.05). The LP diets significantly increased the backfat thickness at first and last ribs, L* (lightness) value of meat color, and muscle fiber density in the longissimus dorsi (P < 0.05). The mRNA expression of fatty acid synthetase (FAS), peroxisome proliferator activated receptor gamma (PPARγ), leptin and acetyl-CoA carboxylase (ACC) was significantly down-regulated, while that of carnitine palmitoyl transferase 1 (CPT1) and myosin heavy chain (MYHC) Ⅱx in the longissimus dorsi muscle was significantly up-regulated by LP diets (P < 0.05). The 16S sequencing analysis showed that the abundance of unidentified Bacteria at phylum level, and Halanaerobium and Butyricicoccus at genus level in the colonic digesta were significantly decreased by LP diet (P < 0.05). The LP diet significantly decreased the observed species of α-diversity in both ileal and colonic microbiota (P < 0.05). Spearman correlation analysis identified a significant positive correlation between the abundance of the ileal genera Streptococcus and L* value at 24 h and 48 h, and a significant negative correlation between unidentified_Ruminococcasceae in both ileum and colon with L* value at 24 h (P < 0.05). Collectively, the LP diet supplemented with lysine, methionine, threonine, and tryptophan could reduce the fecal nitrogen emission without affecting growth performance, and improve meat quality by regulating the antioxidant capacity and gene expression involved in fat metabolism as well as modulating the gut microbiota composition in finishing pigs.